601 Comparison of Sleep Parameters in Children with Achondroplasia and Trisomy 21. (3rd May 2021) - Gustave, Jodi; Gaza, Kaelyn; Marriner, Jennifer; Rani, Seema; Strang, Abigail; Chidekel, Aaron
Abstract: Introduction: Children with achondroplasia and Trisomy 21 (T21) have increased incidence of sleep disturbances including sleep disordered breathing. Abnormal sleep architecture has been documented in children with T21. It is important to continue to analyze sleep parameters in both groups since poor sleep quality is associated with neurocognitive impairment. Methods: Following IRB approval, we performed a retrospective chart review of patients at Nemours/A.I. duPont Hospital for Children in Wilmington, DE with achondroplasia and T21 who underwent an initial polysomnogram (PSG) between 2015 and 2020. We compared sleep architecture parameters between the groups including sleep efficiency, total sleep time (TST), sleep latency, arousal index and concentration of N3 and REM sleep. Results: In patients with achondroplasia (n=49, mean age 5.8 months and 63.3% male), 12% reported restless sleep. PSG data revealed TST of 392 minutes, mean sleep efficiency of 82%, mean sleep latency of 9.4 min, mean arousal index of 40, 22% REM sleep and 32% N3 sleep. In the patients with T21 (n=32, mean age 17.8 months and 50% male), 59% reported restless sleep. PSG data revealed TST of 393 minutes, mean sleep efficiency of 82%, mean sleep latency of 14 minutes, arousal index of 35, 15% REM sleep and 40% N3 sleep. The differences in REM and N3 sleep between the two groups were statistically significant (p-values of 0.001 and 0.04, respectively), but the differences in arousal index, TST and sleep efficiency were not. Conclusion: Our study showed that children with T21 subjectively noted more restless sleep compared to patients with achondroplasia although TST and sleep efficiency were similar. Patients with achondroplasia had a higher arousal index that was not statistically significant. Children with achondroplasia had a shorter sleep latency and more robust REM concentration, likely due to their younger age. There was a higher concentration of N3 sleep in patients with T21. This is likely due to the decrease in REM concentration. In conclusion, it is important to establish expected sleep parameters in patients with achondroplasia and T21 to maximize sleep quality and mitigate negative neurocognitive effects of poor sleep. Support (if any):